Expected Monetary Policy and the Dynamics of Bank Lending Rates - Claudia Kwapil; Johann Scharler (Oesterreichische Nationalbank (OeNB), 2009)
In this paper we explore empirically to what extent expected monetary policy matters for the dynamics of bank lending rates in the U.S., the U.K. and Germany. We find that banks have increasingly behaved in a forward-looking fashion by taking expected changes in monetary policy rates into account when setting lending rates. We document that along with the shifts in monetary policy regimes towards inflation targeting, expected monetary policy has become more important as a determinant of bank lending rates. Overall, our results provide support for the hypothesis that monetary policy has become more effective by successfully influencing private sector expectations.
Keywords: E52; E58; 330; Monetary Policy; Expectations; Interest Rate Pass-Trough